1998
DOI: 10.1002/(sici)1097-0185(199812)252:4<499::aid-ar1>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of proteoglycans in neural tube fluid by β-D-xyloside alters brain enlargement in chick embryos

Abstract: Following neurulation, the anterior end of the neural tube undergoes a dramatic increase in size due mainly to the enlarging of the brain cavity. This cavity is filled with so-called neural tube fluid (NTF), whose positive pressure has been shown to play a key role in brain morphogenesis. This fluid contains a water-soluble matrix, rich in chondroitin sulfate (CS), which has been proposed as an osmotic regulator of NTF pressure genesis. The purpose of the present study is to observe the influence of CS on NTF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…And recently Alonso et al (1998) demonstrated an oncotic gradient in chick embryos older than those used in our study. They showed a significant increase in fluid within the ventricles of HH stage 20 -29 chick embryos after treatment with beta-D-xyloside, and attributed the increase in size of the ventricles of the treated embryos to the increased concentration of chondroitin sulfate-free chains and sodium in the neural tube fluid.…”
Section: Temporal Development Of the Transport Capacity Of The Neuroesupporting
confidence: 55%
“…And recently Alonso et al (1998) demonstrated an oncotic gradient in chick embryos older than those used in our study. They showed a significant increase in fluid within the ventricles of HH stage 20 -29 chick embryos after treatment with beta-D-xyloside, and attributed the increase in size of the ventricles of the treated embryos to the increased concentration of chondroitin sulfate-free chains and sodium in the neural tube fluid.…”
Section: Temporal Development Of the Transport Capacity Of The Neuroesupporting
confidence: 55%
“…It has previously been reported, in chick and rat embryos at early stages of development, that E-CSF exerts positive pressure against the neuroepithelial walls to generate an expansive force that drives morphogenesis Desmond and Jacobson, 1977;Alonso et al, 1998Alonso et al, , 1999Desmond et al, 2005). However, in recent years new roles for E-CSF have been demonstrated in the behaviour of neuroepithelial cell precursors, as it contributes to the regulation of the survival, proliferation, and neural differentiation of the neuroepithelial progenitor cells during early (Gato et al, 2005) and late development (Mashayekhi et al, 2002;OwenLynch et al, 2003;Miyan et al, 2003), as well as collaborating with the isthmic organiser in regulating mesencephalic gene expression (Parada et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, certain neurons send processes into the ventricular space, suggesting that their activity may be connected with regulating CSF homeostasis (Vigh and Vigh-Teichmann, 1998). CSF contains hormones, proteoglycans and ions, and its composition varies between ventricles and over time, suggesting a changing function for the ventricles during development (Alonso et al, 1998;Skinner and Caraty, 2002). Abnormalities in brain ventricle structure can lead to hydrocephaly, one of the most common birth defects (McAllister and Chovan, 1998;Rekate, 1997), and abnormal brain ventricle size and development have been correlated with mental health disorders such as autism and schizophrenia (Hardan et al, 2001;Kurokawa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%